2021
DOI: 10.1101/2021.08.05.455235
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential use of multiple genetic sex determination systems in divergent ecomorphs of an African crater lake cichlid

Abstract: African cichlid fishes not only exhibit remarkably high rates of speciation but also have some of the fastest evolving sex determination systems in vertebrates. However, little is known empirically in cichlids about the genetic mechanisms generating new sex-determining variants, what forces dictate their fate, the demographic scales at which they evolve, and whether they are related to speciation. To address these questions, we looked for sex-associated loci in full genome data from 647 individuals of Astatoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 73 publications
(118 reference statements)
1
26
1
Order By: Relevance
“…Transposable element dynamics are increasingly recognised as major drivers of evolutionary innovation, and their analysis is greatly facilitated by the use of long-read sequencing technologies 41,42 . For example, the location of TE insertions can influence the expression of nearby genes and induce phenotypic variation 43,44 . The diversity of transposons varies substantially between organisms, with teleost fish genomes containing greater TE diversity compared to other vertebrates, such as mammals 41,45 .…”
Section: Transposon Expansion Is Driving Genome Size Evolution In Not...mentioning
confidence: 99%
“…Transposable element dynamics are increasingly recognised as major drivers of evolutionary innovation, and their analysis is greatly facilitated by the use of long-read sequencing technologies 41,42 . For example, the location of TE insertions can influence the expression of nearby genes and induce phenotypic variation 43,44 . The diversity of transposons varies substantially between organisms, with teleost fish genomes containing greater TE diversity compared to other vertebrates, such as mammals 41,45 .…”
Section: Transposon Expansion Is Driving Genome Size Evolution In Not...mentioning
confidence: 99%
“…In fact, recent evidence suggests that TEs have contributed further to the astonishing ecomorphological diversity of East African cichlids. Two recent studies have identified insertions of DNA TEs and retrotransposons close to opsin genes and to gsdf, with potentially important consequences for visual and sex determination systems, respectively [88,89]. It is appealing to contemplate TE-derived cis-regulatory activity driving or fueling adaptive radiation, in lieu of low genetic diversity.…”
Section: Trends In Geneticsmentioning
confidence: 99%
“…Using such an approach, several studies identified genes associated with interspecific variation in craniofacial profiles, jaw attributes, colour patterns and sex determination systems. The increase in genomic resources and the low costs of whole genome sequencing are also leading to an increase in genome-wide association studies in wild populations giving unprecedented insights into intraspecific variation [57,59]. A commonality between all these studies is that often the causal variants are in non-coding regions, hence establishing methods to edit non-coding regions will facilitate the dissection of their functional role.…”
Section: Discussionmentioning
confidence: 99%